Interleukin 2-induced increase of vascular permeability without decrease of the intravascular albumin pool. - Ballmer-Weber, B. K. (Nature Publishing Group, 1995)
Interleukin 2 (IL-2) exhibits anti-tumour activity. High-dose IL-2 regimens are limited by side-effects such as pulmonary oedema and a systemic vascular leak. The mechanisms by which IL-2 mediates transvascular fluid and protein losses in humans are largely unknown. We have, therefore, measured the transcapillary escape rate (TER) of albumin as a reflection of the vascular permeability by injecting [125I]albumin (5 microCi i.v.). In ten melanoma patients pretreated with interferon alpha (IFN-alpha) TER of albumin was measured before and after IL-2 injections (1.5 x 10(6) Cetus-U. s.c. daily for 4 days). The TER of albumin increased from 9.4 +/- 2.7% h-1 before to 14.9 +/- 3.3% h-1 (P < 0.001) after IL-2 injections and the absolute outflux of albumin (Jalb) from 159 +/- 28 mg kg-1 h-1 to 261 +/- 44 mg kg-1 h-1 (P < 0.001), whereas the intravascular albumin pool remained stable (136 +/- 19 g vs 136 +/- 18 g). IL-2 and IL-6 were not detectable in the plasma prior to IL-2 injections and increased to 549 +/- 315 U ml-1 (P < 0.001) and 7 +/- 6 pg ml-1 (P < 0.01), respectively, after IL-2 administration. In conclusion, IL-2 increases the vascular permeability in humans, without affecting the intravascular albumin pool. This suggests that mechanisms such as the lymphatic return can compensate for the severe transendothelial fluid/albumin losses.